2013
DOI: 10.1097/nen.0b013e3182965886
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson Disease Affects Peripheral Sensory Nerves in the Pharynx

Abstract: Dysphagia is very common in patients with Parkinson’s disease (PD) and often leads to aspiration pneumonia, the most common cause of death in PD. Unfortunately, current therapies are largely ineffective for dysphagia. As pharyngeal sensation normally triggers the swallowing reflex, we examined pharyngeal sensory nerves in PD for Lewy pathology. Sensory nerves supplying the pharynx were excised from autopsied pharynges obtained from patients with clinically diagnosed and neuropathologically confirmed PD (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 55 publications
4
98
0
8
Order By: Relevance
“…A reduction of sensitivity can be present in the pharynx [35] as describe by Mu et al [35]. The pharynx has an important role in the bolus conduction, and also, in triggering the swallowing reflex.…”
Section: Non-motors Aspects Of Dysphagia In Parkinson's Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…A reduction of sensitivity can be present in the pharynx [35] as describe by Mu et al [35]. The pharynx has an important role in the bolus conduction, and also, in triggering the swallowing reflex.…”
Section: Non-motors Aspects Of Dysphagia In Parkinson's Diseasementioning
confidence: 93%
“…The pharynx has an important role in the bolus conduction, and also, in triggering the swallowing reflex. Mu et al [35] found a large number of muscular fibers atrophied in the pharynx, an additionally alteration in sensorial nerves, such as: glossopharyngeal nerve, pharyngeal sensory branch of the vagus nerve and the internal superior laryngeal nerve. This sensorial alteration leads to an insufficient auto-perception of swallowing problems and several of PD patients do not complaint about dysphagia.…”
Section: Non-motors Aspects Of Dysphagia In Parkinson's Diseasementioning
confidence: 99%
“…a-synuclein aggregates have been detected in the pharyngeal motor and sensory branch of vagus nerve, in the glossopharyngeal nerve and in the internal superior laryngeal nerve in PD patients with dysphagia [8,9]. Lewy bodies have also been found in the dorsal vagus ganglion and parasympathetic sacral nuclei, as well as in the enteric nervous system, and cardiac and pelvic plexus, even in early disease stages [10e14].…”
Section: Parkinson's Disease Is a Determinant Of Neuropathymentioning
confidence: 99%
“…Recent comprehensive postmortem neuropathologic studies of PD patients have indicated that brain pathology (Lewy neurites and Lewy bodies) in PD originates in the olfactory bulb and visceromotor projections of dorsal nucleus of the glossopharyngeal and vagal nerves in medulla oblongata years prior to involvement of nigrostriatal pathway and onset of somatomotor dysfunction 7 . Furthermore, these histopathologic observations have shown atrophic and denervated pharyngeal constrictors and cricopharyngeus myofibers 8 ; axonal degenerative changes in vagal and sympathetic motoneurons innervating pharyngeal constrictors and cricopharyngeus 9 , along with degenerative changes of predominantly sensory internal superior laryngeal branch of the vagus nerve 10 . Collectively these central and peripheral autonomic sensorimotor impairments in dysphagic PD patients may explain compromised cough reflex 11 , delayed swallow reflex 3, 12 , pharyngeal peristaltic incoordination 3, 13 and incomplete UES relaxation 3, 14 .…”
mentioning
confidence: 90%